2017
DOI: 10.1080/13691058.2017.1372632
|View full text |Cite
|
Sign up to set email alerts
|

From risky behaviour to sexy adventures: reconceptualising young people’s online sexual activities

Abstract: Western discourses about young people and sexuality centre around the concept of risk. Anxieties have been fuelled by the increasing popularity of social media and practices such as 'sexting' and watching 'sexually explicit' materials online. Research has shown however that such risk discourses mainly serve to moralise about, pathologise and police particular behaviours and children. In order to counter such paternalism, researchers advocated a reconceptualisation of youth not as passive victims, but as active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 62 publications
3
17
0
10
Order By: Relevance
“…Furthermore, the characteristics of youth differ according to who defines it. Naezer (2018), for example, found that the social category of age had little meaning to the young people she studied. Scholars increasingly urge professionals and policy makers to start from emic perspectives of young people to avoid listening to young people in a tokenistic manner and setting up inappropriate interventions for them (Bordonaro, 2012; Payne, 2012).…”
Section: Conceptualizing Youth: Scholarship On Age and Young Motherhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the characteristics of youth differ according to who defines it. Naezer (2018), for example, found that the social category of age had little meaning to the young people she studied. Scholars increasingly urge professionals and policy makers to start from emic perspectives of young people to avoid listening to young people in a tokenistic manner and setting up inappropriate interventions for them (Bordonaro, 2012; Payne, 2012).…”
Section: Conceptualizing Youth: Scholarship On Age and Young Motherhoodmentioning
confidence: 99%
“…Sex education is predominantly developed from an adult, heterosexual perspective that focuses on risks but insufficiently includes diverse perspectives from youngsters themselves (Naezer et al, 2017). Moreover, sexual double standards label boys who have sex as “cool” and girls as “sluts” (Naezer, 2018; Vanwesenbeeck, 2011).…”
Section: Socioeconomic Context Of Young Motherhood In the Netherlandsmentioning
confidence: 99%
“…For adolescents, the use of information and communication technologies (ICTs) is an integral part of their daily lives [ 1 ]. ICTs have become powerful tools for education, identity formation, entertainment, managing/maintaining romantic relationships, and sexual exploration and expression [ 2 , 3 ]. A contemporary form of sexual online expression is sexting which is defined as sharing sexually suggestive text messages or self-produced sexually explicit images like photos or videos (sexts) via social media or smartphone apps [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…W dyskusji na temat oddziaływania tego typu materiałów na młodzież można spotkać się z opinią, że temat szkodliwości tej sfery internetowej stał się wyolbrzymiony (Spišák, 2016). Istnieją koncepcje, w ramach których zakłada się, że ze względu na łatwą dostępność materiałów pornograficznych oraz nakładającej się na ten fakt specyfiki wieku dojrzewania, związanej z odkrywaniem własnej seksualności, poszukiwanie filmów, zdjęć zawierających tło seksualne jest naturalnym elementem procesu rozwojowego (Naezer, 2018). Niemniej jednak badacze podkreślają, że narażenie na "konsumpcję" materiałów pornograficznych prowadzi do akceleracji zjawiska sekstingu, tworzy nega-…”
Section: Dyskusjaunclassified